2018
DOI: 10.1111/jch.13217
|View full text |Cite
|
Sign up to set email alerts
|

Associations of overweight/obesity and socioeconomic status with hypertension prevalence across racial and ethnic groups

Abstract: Racial/ethnic disparities in the prevalence of diagnosed hypertension are persistent but may be partially explained by racial/ethnic differences in weight category and neighborhood socioeconomic status. The authors compared hypertension prevalence rates among 4 060 585 adults with overweight or obesity across 10 healthcare systems by weight category and neighborhood education level in geographically and racially diverse individuals. Data were obtained from electronic health records. Hypertension was defined as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…For example, the rates of elevated blood pressure identified in this study corroborate with studies of black individuals (primarily African Americans) within in the US; however, refugees are a unique group and comparison should be taken with caution. [23,24,25] Research available for comparison has identified elevated hypertension risk in samples which combined African refugees (including Congolese) vs. other refugee groups. [8] Hypertension risk has also been found to increase by 6.6-6.8% for each additional year a refugee resides in the US.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rates of elevated blood pressure identified in this study corroborate with studies of black individuals (primarily African Americans) within in the US; however, refugees are a unique group and comparison should be taken with caution. [23,24,25] Research available for comparison has identified elevated hypertension risk in samples which combined African refugees (including Congolese) vs. other refugee groups. [8] Hypertension risk has also been found to increase by 6.6-6.8% for each additional year a refugee resides in the US.…”
Section: Discussionmentioning
confidence: 99%
“…As described in detail elsewhere, the PORTAL cohort includes more than 5 million individuals with overweight and obesity and reflects the underlying regional race, ethnicity, and neighbourhood education and income distributions of the participating health systems. In a previous analysis of this cohort, the prevalence of hypertension was greater for Blacks, American Indians/Alaska Natives, Asians, and Native Hawaiians/Pacific Islanders compared with Whites despite being in the same BMI category and neighbourhood education level . Furthermore, racial/ethnic minorities in this cohort had a higher burden of prediabetes and diabetes at lower BMIs than Whites .…”
Section: Methodsmentioning
confidence: 99%
“…[4] The association between cardiovascular disease and their risk factors and socioeconomic factors has been reported in many studies. [12][13][14] A relationship between social determinants and lifestyle behaviors like physical inactivity, tobacco smoking, and dietary habits and cardiovascular disease mortality has been reported [15][16] as well as the relationship between Socio-Economic Status (SES) and Type-2 diabetes mellitus(T2DM), [17] hypercholesterolemia, [18] obesity and high blood pressure [19] has been documented. The historical city of Yazd has a new urban texture along with the old area.…”
Section: Introductionmentioning
confidence: 99%